Beyond Victim Blaming: Students' Perceptions of Bystanders Who Fail to Intervene. Issue 3 (2nd July 2020) - Holtzman, Mellisa
ABSTRACT: Bystander intervention education has been a common feature on college campuses for more than a decade. Although research has explored the degree to which bystander training influences students' attitudes toward sexual assault, their perceptions of their own efficacy to intervene, and their intentions to help others, very little is known about how such training impacts students' perceptions of bystanders who knowingly fail to intervene. In other words, what impact is bystander education having on broader expectations for bystander behaviors? This research addresses this question using in-depth interview data from 51 college students. Results suggest that although students report a general expectation that bystanders should intervene in sexually threatening situations, intrapersonal, microsystem, exosystem, and macrosystem factors, nonetheless, interact with one another to excuse or justify nonintervention by bystanders. Implications for campus programming are discussed.